JAPANESE LEARNING AT SMA NEGERI 30 JAKARTA (Ethnography Research) - Karundeng, Christofeira Zita; Ekowati, Sri Harini; Darmahusni, Darmahusni (IJLECR (International Journal of Language Education and Cultural Review), 2018)
This research is aimed to get a deep understanding towards Japanese learning in 30 Senior High School in Jakarta. This research uses qualitative approach with ethnography method. This research was done in the 9th grade for 4 months, from Dec 2017 until March 2018. The data was gained from observation, interview, field note and documentation right from the location of the research. The data was analysed by using Spradley model, consisting of culture domain, taxonomy, components and theme. The source of research to get the data is from Japanese teacher and all things related with the process of Japanese learning. The teacher and students play an important role during the process of learning. The results of the research are: 1) The four objectives which need to be achieved in Japanese learning are : listening skill (choukai), speaking (kaiwa), reading (dokkai), and writing (sakubun) and so that the students have selling point when they are about to work. 2) The curriculum being used is 2013 curriculum. 3) The teaching material being used by the teacher is adjusted with the text book which is sakura book, supporting book and the syllabus. 4) the teaching strategy and the method is lecturing, exercises, assignments based on theme. 5) media used such as tapes, picture cards, learning CD, japanesse language and culture DVD. 6) evaluation of processes and outcomes.